AYURVEDA AND RELIGION IN CANADA: A CRITICAL LOOK AT NEW AGE AYURVEDA FROM THE INDIAN DIASPORA PERSPECTIVE - Natalia Abraham (Religious Studies, McGill University, Montreal, 2003)
This thesis examines how physicians in the Indian diaspora living in Canada - both those trained in Ayurveda in lndia (vaidyas) and those trained in Western medicine in lndia (MDs) - view the practice of Ayurveda in Canada. More specifically, it examines how their views have been influenced by New Age thought in general and Transcendental Meditation in particular and how these perceptions reflect the changing relation of religion and Ayurvedic medicine. It is the intent of this thesis to show that Ayurveda in Canada exists mainly as part of the greater New Age movement, as a transformed system that is inspired by both Hinduism and New Age thought, and that this transformation of Ayurveda evokes two distinct responses from lndian diaspora medical personnel in Canada - one unsupportive and one partially supportive. To the dismay of "traditional" lndians and to the praise of "modem" lndians, New Age Ayurvedic organizations strongly emphasize their version of "spirituality" as the primary goal of Ayurveda, whereas lndian forms of Ayurveda - both in the past and today - generally approach religion and spirituality secondarily. Thus, the role of religion and spirituality become major controversial issues in New Age Ayurveda. From the "traditional" point of view, the commercial achievements of New Age organizations (such as the Transcendental Meditation Movement) are not indicative of a successful introduction of Ayurveda in North America and run contrary to classical Ayurvedic principles, with regard to religious and medical practice. But, from the "modem" point of view, the New 11Age Ayurvedic emphasis on spirituality is indicative of an inevitable evolution of the system in North America.